2014
DOI: 10.3109/13561820.2014.942776
|View full text |Cite
|
Sign up to set email alerts
|

The interprofessional clinical experience: interprofessional education in the nursing home

Abstract: The interprofessional clinical experience (ICE) was designed to introduce trainees to the roles of different healthcare professionals, provide an opportunity to participate in an interprofessional team, and familiarize trainees with caring for older adults in the nursing home setting. Healthcare trainees from seven professions (dentistry, medicine, nursing, nutrition, occupational therapy, optometry and social work) participated in ICE. This program consisted of individual patient interviews followed by a team… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
47
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(47 citation statements)
references
References 5 publications
0
47
0
Order By: Relevance
“…Only one study was published in 1981 and the other 6 were published between 2012 and 2015 indicating the recently increasing interest in research in this area. All publications originated from the United States . Three originated from the same centre, University of Alabama at Birmingham Geriatric Education Center, with 2 of them reporting on the same training experience and sample .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Only one study was published in 1981 and the other 6 were published between 2012 and 2015 indicating the recently increasing interest in research in this area. All publications originated from the United States . Three originated from the same centre, University of Alabama at Birmingham Geriatric Education Center, with 2 of them reporting on the same training experience and sample .…”
Section: Resultsmentioning
confidence: 99%
“…All publications originated from the United States . Three originated from the same centre, University of Alabama at Birmingham Geriatric Education Center, with 2 of them reporting on the same training experience and sample . The earlier one reported more details on the content and methodology of the programme, while the most recent one on the outcomes …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…There has been considerable literature examining student attitudes to ageing, the majority focusing on nursing and medical students (Gonzales, Morrow-Howell, & Gilbert, 2010;King, Roberts, & Bowers, 2013;Lea, Mason, Eccleston, & Robinson, 2015;Rodgers & Gilmour, 2011) and only a limited number on students from other health professions (Sheppard et al, 2015;Zambrini, Moraru, Hanna, Kalache, & Nuñez, 2008). A recent study by Lea et al (2015) found that for second year nursing students, a supported residential aged care placement can influence attitudes towards older adults and working in aged care postgraduation.…”
Section: Introductionmentioning
confidence: 99%